A formação do profissional de educação física para atuar na atenção básica em saúde: uma análise a partir do Projeto Político Pedagógico do Curso de Licenciatura em Educação Física da Universidade Federal do Pará / Campus Belém. - ARAUJO, Silvio Marcio Muniz de (2020)
This work aimed to analyze the debate about the formation and insertion of the Physical Education Professional (PEF) in the sphere of public health policies through reflections made by various authors such as (BACHETTI, 2014, CARVALHO, 2001, PATROCÍNIO, 2012), bringing to light questions about physical activities / corporal practices in health care and the possibility of Physical Education as a way to promote collective health. The purpose of this study is to study the curricular proposal of the Physical Education Course of UFPA, Belem Campus, adopted from the year 2012. It also has the following guiding question: the Physical Education curriculum of UFPA, Campus Belem, prepares the egress to meet the demand of Basic Health Care? In order to do so, it was presented, historically, how the consolidation of the Unified Health System (SUS) and the Basic Health Care (ABS) in Brazil was presented and for this purpose we tried to portray the transformations and ruptures existing in the guarantee of rights health of the Brazilian population. It was verified how the process of integrating PE in public health occurred with the insertion of PEF into ABS. It was understood through the Pedagogical Political Project (PPP) of the Physical Education Course of UFPA, whether or not it contemplated a training that would attend to the performance of the graduates in ABS. Documentary and qualitative research was then carried out by analyzing the legal frameworks (legislation) that make up the office of the PEF, such as resolutions, decrees, guidelines, among others. Scientific articles, periodicals and monographs were also analyzed. In view of this, it was observed that the curriculum of the UFPA, contains within its scope, disciplines that contemplate, not intentionally, the performance of the egress in the ABS, but none of its contents deal with the SUS debate, which the need to address this subject or in specific discipline, or as a cross-cutting theme in relevant disciplines during the academic periods, such as Public Policies in EF, Sports and Leisure, and in the supervised stage, when the instrumentalization of the techniques may be more refined.